Price Disparity Based on Trip Origins - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2005)
This paper examines the extent of third-degree price discrimination on dense intercontinental long-haul routes in economy and business cabins according to a comparable list of fare conditions. Based on a survey of return fares in economy and business cabins, significant price disparities are observed across all routes for intercontinental round trips originating from particular regions, and for geographically opposite markets, ie a round trip from a city in region A to a city in region B and back can costs substantially more than a round trip taken from the same city in region B to the same city in region A and back. The price disparity depends on the region of travel (eg transpacific versus Europe-Asia) as well as the market structure (ie the competitive nature of each route). The level of route-specific competition has a statistically significant and negative impact on the route-mean economy fares and the difference of geographically opposite business fares. This has practical implications for revenue management, as many passengers holding tickets of vastly different value currently may have the same access to seat inventory.